Comparison of serum neurodegenerative biomarkers among hospitalized COVID‐19 patients versus non‐COVID subjects with normal cognition, mild cognitive impairment, or Alzheimer's dementia. Issue 5 (13th January 2022) - Frontera, Jennifer A.; Boutajangout, Allal; Masurkar, Arjun V.; Betensky, Rebecca A.; Ge, Yulin; Vedvyas, Alok; Debure, Ludovic; Moreira, Andre; Lewis, Ariane; Huang, Joshua; Thawani, Sujata; Balcer, Laura; et al.
Abstract: Introduction: Neurological complications among hospitalized COVID‐19 patients may be associated with elevated neurodegenerative biomarkers. Methods: Among hospitalized COVID‐19 patients without a history of dementia (N = 251), we compared serum total tau (t‐tau), phosphorylated tau‐181 (p‐tau181), glial fibrillary acidic protein (GFAP), neurofilament light chain (NfL), ubiquitin carboxy‐terminal hydrolase L1 (UCHL1), and amyloid beta (Aβ40, 42) between patients with or without encephalopathy, in‐hospital death versus survival, and discharge home versus other dispositions. COVID‐19 patient biomarker levels were also compared to non‐COVID cognitively normal, mild cognitive impairment (MCI), and Alzheimer's disease (AD) dementia controls (N = 161). Results: Admission t‐tau, p‐tau181, GFAP, and NfL were significantly elevated in patients with encephalopathy and in those who died in‐hospital, while t‐tau, GFAP, and NfL were significantly lower in those discharged home. These markers correlated with severity of COVID illness. NfL, GFAP, and UCHL1 were higher in COVID patients than in non‐COVID controls with MCI or AD. Discussion: Neurodegenerative biomarkers were elevated to levels observed in AD dementia and associated with encephalopathy and worse outcomes among hospitalized COVID‐19 patients.